Islamic Sustainable Financial Literacy: Offering the Concept of Sustainable Financial Literacy Based on Maqashid Shariah - Emiliyani Wahyuni; Rizal Rizal; Chitra Indah Sari (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose:This study develops a conceptual framework of Islamic Sustainable Financial Literacy (ISFL) by integrating Maqashid Shariah principles with sustainability perspectives. Existing financial literacy models largely focus on technical and cognitive aspects, with limited attention to ethical, social, and environmental dimensions. This research addresses this gap by proposing a holistic literacy model aligned with Islamic values and sustainable development.Design/Methodology:The study employs a qualitative conceptual approach using a systematic literature review. Academic articles, Islamic economic literature, and relevant policy documents were analyzed. Thematic content analysis was applied to identify and synthesize key concepts related to financial literacy, sustainability, and Maqashid Shariah.Findings:The results show that sustainable Islamic financial literacy extends beyond knowledge of Sharia-compliant products. The ISFL framework consists of four dimensions: cognitive, affective, behavioral, and socio-ecological. Key indicators include Sharia knowledge, financial capability, eco-social awareness, Islamic ethical orientation, and active economic participation. These dimensions are conceptually linked to Maqashid Shariah objectives and the Sustainable Development Goals (SDGs)..Practical Implications:The proposed framework provides guidance for policymakers, Islamic financial institutions, and educators in designing financial literacy programs that integrate ethical, social, and environmental considerations. It also supports the development of more comprehensive literacy measurement tools and sustainability-oriented financial education.Originality/Value:This study offers a novel integrative model of Islamic Sustainable Financial Literacy by explicitly combining Islamic financial literacy, Maqashid Shariah, and sustainability principles. The framework enriches the financial literacy literature and contributes to the advancement of Islamic finance and sustainable development discourse..